Persistent Supravenous Erythematous Eruption (PSEE): A scoping review on an adverse effect related to Docetaxel infusion (Research, Society and Development, 2022)
Objectives: To identify and synthesize scientific evidence about Persistent Supravenous Erythematous Eruption (PSEE), in order to characterize it and provide support to clinical practice in differentiating this event from Docetaxel extravasation. Methods: scoping review, according to Joanna Briggs Institute. The PCC strategy was used to formulate the research question. Research was carried out in four electronic databases: PubMed, Embase, CINAHL and VHL/IBECS. Data collection took place from February to May 2021, aiming at a time frame of the last 10 years. The data extracted from the selected articles were analyzed and synthesized in a narrative way. Results: a total of 474 records were retrieved and 7 studies were kept for review. Most of the publications (4) were of the case report type, being possible to have the main information, extracted, in the form of tables and categorization of these in: Possible causes of PSEE; PSEE pathophysiology; Frame characterization; Prevention measures; Management of PSEE. Conclusions: Evidence raised about PSEE allowed its characterization and differentiation in relation to extravasation, with the possibility of guiding correct management and more assertive care of nursing and other components of the health team to a toxicity inherent to the chemotherapy treatment.